2019
DOI: 10.1074/jbc.ra118.005932
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the sites of the lipoprotein lipase (LPL)–angiopoietin-like protein 4 (ANGPTL4) interaction provides mechanistic insight into LPL inhibition

Abstract: Edited by George M. CarmanCardiovascular disease has been the leading cause of death throughout the world for nearly 2 decades. Hypertriglyceridemia affects more than one-third of the population in the United States and is an independent risk factor for cardiovascular disease. Despite the frequency of hypertriglyceridemia, treatment options are primarily limited to diet and exercise. Lipoprotein lipase (LPL) is an enzyme responsible for clearing triglycerides from circulation, and its activity alone can direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 58 publications
1
41
1
Order By: Relevance
“…Second, the concentration of ANGPTL4 used in those studies would have, at least in our hands, resulted in irreversible inhibition of LPL before the first time point. Third, there was no time dependence in deuterium uptake within the putative ANGPTL4 interaction sites, which is surprising given the high K i that was reported (49). Similar caveats also confound the findings in a second HDX-MS-based study (54), which concludes that ANGPTL4 binds to another region in LPL that harbors the catalytic site (i.e., residues 130 to 162).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Second, the concentration of ANGPTL4 used in those studies would have, at least in our hands, resulted in irreversible inhibition of LPL before the first time point. Third, there was no time dependence in deuterium uptake within the putative ANGPTL4 interaction sites, which is surprising given the high K i that was reported (49). Similar caveats also confound the findings in a second HDX-MS-based study (54), which concludes that ANGPTL4 binds to another region in LPL that harbors the catalytic site (i.e., residues 130 to 162).…”
Section: Discussionmentioning
confidence: 91%
“…The biological importance of ANGPTLs in regulating plasma triglyceride homeostasis by inhibiting LPL activity has been firmly established by human and mouse genetics (15)(16)(17)(18)(19) and by pharmacological studies (7,(45)(46)(47), but the molecular mechanism for LPL inactivation has remained controversial. One view holds that ANGTPL4 is a reversible and noncompetitive LPL inhibitor with an inhibition constant (K i ) of 0.9 to 1.7 μM (48,49), but that view relies on studies performed in the presence of deoxycholate (a detergent that stabilizes LPL) (4,50). Moreover, the low inhibitory efficacy of ANGPTL4 in those studies is difficult to reconcile with the fact that low nanomolar concentrations of ANGPTL4 readily inhibit triglyceride hydrolysis by low nanomolar concentrations of LPL (4-6, 29, 30, 43, 51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that Lactobacillus probiotic bacteria have an effect to lower body fat levels with higher ANGTPL4 expression levels [19]. The ANPTL4 gene is responsible for the inhibition of LPL, which leads to a decrease in fat storage [20]. Studies in mice have shown that the ANGPTL4 gene and the intestinal microbiota control body weight [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting reports exist on the regulation of HL activity by ANGPTL4. Koster et al, using global ANGPTL4 KO mice and liver-specific overexpression of ANGPTL4, and Gutsell et al, using an in vitro system, have shown that ANGPTL4 does not affect HL activity(28,43). In contrast, Lichtenstein et al observed that adenovirus-mediated overexpression of ANGPTL4 inhibits postheparin HL activity(12).…”
mentioning
confidence: 99%